ANALISIS KEBUTUHAN SUMBER DAYA MANUSIA UNIT ASSEMBLING RAWAT JALAN MENGGUNAKAN METODE ANALISIS BEBAN KERJA KESEHATAN (ABK-KES) UNTUK MENINGKATKAN EFISIENSI KERJA DI RS X - Ramalinda, Dola (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
Hospitals are required to have qualified health workers and in accordance with the amount of their workload in supporting the effectiveness of hospital service functions. So that there is no overload so that it can affect the quality and quantity of work. The purpose of this study is to determine the needs of health human resources in the type of assembling work and outpatient analysis at X Hospital. This study uses a descriptive qualitative research method using interviews and observations to determine available working hours, workload standards, and supporting task standards based on the health workload analysis method (ABK-Kes). The results of this study show that the Available Working Time of the assembling and outpatient analysis employees is 96,780 minutes/year with the results not in accordance with the effective working hours (JKE) which should be 72,000 minutes/year. The results of this study also prove that 4 competent health workers are needed. However, the number of assembling and outpatient analysis employees at the hospital only has 1 employee. The conclusion is that employees in the medical record unit of the assembling and outpatient analysis section still need additional health human resources employees so as not to experience an overload.